(untitled) (Update Dental College Journal, 2024)
Introduction: Nasolabial cyst is a rare non-odontogenic soft tissue cyst of the nasal alar region with an occurrence of 0.7% cases out of all maxillofacial cysts. Clinically, it mostly presents as painless swelling in the nasal region. Diagnosis is made based on history and clinical examination. Aspiration, radiographic examination, and cross-sectional scans assist in ruling out other odontogenic or non-odontogenic pathologies and also help in locating the lesion. Case report: This paper documents case report of nasolabial cyst in a 30-year-old male patient. This article presents clinical diagnosis, investigations, and surgical management of the lesion, along with a review of literature. Conclusion: There are various treatment options for the management of NLC. We used a sublabial surgical approach to excise the lesion, followed by histopathological examination, which further confirmed the diagnosis. This lesion has rare reoccurrence and should be considered in differential diagnosis for swelling in nasal alar region. Update Dent. Coll. j: 2024; 14(2): 31-35